Site formation process of the Dadong Paleolithic site in Jilin province, China: A geoarchaeological approach - Lian, Huiru; Xu, Ting; An, Wenrong; Zhu, Yujin; Shi, Hongwei; Zhao, Ying; Chen, Kunlong (Frontiers in Earth Science, 2023)
The Dadong site, located in the Changbaishan region of Jilin province, China, is an important Upper Paleolithic site characterized by its large distribution area and abundant stone artifacts. This study presents a geoarchaeological study of a newly excavated area of this site. Soil micromorphology, particle size analysis, and pH measurements were used to reconstruct the site formation process from around 60 ka to the present. Additionally, this study examines the impact of volcanic eruptions and local geomorphology on ancient human adaptation in this area. This paper also investigates the effects of post-depositional processes, particularly freeze-thaw, on the distribution of lithics. This study is the first soil micromorphological study of a Paleolithic site in Northeast China, and is important for studying the changes of the Pleistocene environment in this region as well as the development of microblade technology in Northeast Asia.